MEMANFAATKAN ENERGI PADA SOLAR CELL UNTUK PARA NELAYAN PESISIR KEP. BANGKA BELITUNG - Yudhi, Yudhi; Ocsirendi, Ocsirendi; Dharta, Yuli; Saputra, Gillang; Hera, Hera (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2024)
The Bangka Belitung Islands are an archipelagic area which is located at 104°50' to 109° East Longitude and 0°50' to 4°10' South Latitude, there are 6 districts and 1 municipality, and with a population of 1,473,165 people. Bangka Belitung is famous for its tin mines, almost 80% of its tin production comes from Bangka Belitung, apart from that, the marine sector also has a distribution role in regional PAD supplies. With the support of fishing boats, fishery products in 2022 will be 196,704 tons/year. To increase fishing capacity in the future, facilities are needed that can support more fishing capacity, apart from ships with larger capacity, they must also be accompanied by other facilities, namely in terms of energy, both for engines and for lighting. To develop renewable energy to support the maritime sector, a system is needed to supply energy, especially to fishing boats, to reduce fuel dependency. By using a clean and efficient energy-generating tool, namely by using a solar cell, with a capacity of 100 wp, a 12Volt/40 HA battery can produce 480 watts of power, so you can light 10 lights with a capacity of 15 watts for 5 hours, meaning you can save fuel by 20-30%.